2019
DOI: 10.1007/s10886-019-01054-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Male-Produced Aggregation Pheromone of the Bean Flower Thrips Megalurothrips sjostedti (Thysanoptera: Thripidae)

Abstract: Aggregation of the bean flower thrips, Megalurothrips sjostedti (Trybom) (Thysanoptera: Thripidae), has been observed on cowpea, Vigna unguiculata (L.) Walp. To understand the mechanism underpinning this behavior, we studied the responses of M. sjostedti to headspace volatiles from conspecifics in a four-arm olfactometer. Both male and female M. sjostedti were attracted to male, but not to female odor. Gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…Characterization of the headspace volatiles of M. usitatus revealed one component present only in male odors, and identified as (2 E ,6 E )‐farnesyl acetate. The compound was unique and structurally different from the active components of the aggregation pheromones of thrips identified so far, including another species M. sjostedti from the same genus recently reported . In thrips, aggregation pheromones have now been identified from four species including F. occidentalis , F. intonsa , T. palmi and M. sjostedti in three different genera .…”
Section: Discussionmentioning
confidence: 64%
“…Characterization of the headspace volatiles of M. usitatus revealed one component present only in male odors, and identified as (2 E ,6 E )‐farnesyl acetate. The compound was unique and structurally different from the active components of the aggregation pheromones of thrips identified so far, including another species M. sjostedti from the same genus recently reported . In thrips, aggregation pheromones have now been identified from four species including F. occidentalis , F. intonsa , T. palmi and M. sjostedti in three different genera .…”
Section: Discussionmentioning
confidence: 64%
“…The males form aggregations on the leaves, while the females spend most of their time in the flowers 9 . Although two components of a male-produced aggregation pheromone, which attracts both males and females, have been identified and investigated with olfactometer experiments 27 , there have been no close-range studies of the mating behaviour. Our pilot observations indicated that there were some distinct and unexpected differences from the behaviour we observed in F. occidentalis 20 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The difference between fighting in the two lineages is likely due to the variation in type and quantity of male-produced pheromones. Males interact over extended periods, so a pheromone may be involved as were found with males of sandfly, F. occidentalis, F. intonsa, M. sjostedti (Trybom) and T. palmi (Karny) (Akella et al, 2014;Hamilton et al, 2005;Jones and Hamilton, 1998;Kirk, 2017;Niassy et al, 2019;Zhang et al, 2011). It has been reported that a male F. occidentalis produces pheromone during aggregation.…”
Section: Tablementioning
confidence: 93%